The effect of coconut water and benzyl amino purine (BAP) addition to the growth of pineapple from Sipahutar North Sumatera in vitro condition - Insani, Harifah; Harahap, Fauziyah; Setya Diningrat, Diky (International Journal of Biological Research, 2018)
Background: Pineapple fruit used in this study was obtained from Sipahutar sub-district, North Tapanuli regency, North Sumatra which was a superior commodity fruit. Propagation of the Sipahutar pineapple plant was conducted vegetatively using bud stems and crown shoots, but the amount was limited to be planted in large areas. Therefore, propagation through tissue culture techniques could be used as an alternative solution.Objective: Explants source were taken from plantlets in vitro aged 3 months were grown on Murashige and Skoog (MS) basic medium with the addition of Indole Acetic Acid (IAA) 1 ppm.Methods: Sipahutar pineapple tissue culture work has been done in YAHDI Plant Tissue Culture Laboratory, Medan. The study design used a factorial completely randomized design. The first factor is coconut water with concentration of 0%, 10%, 20%, and 30%, second factor is Benzyl Amino Purine (BAP) with concentration 0 ppm, 2 ppm and 4 ppm, so there were 12 combination with 3 repetition.Result: The results showed that the addition of coconut water on MS base medium with IAA of 1 ppm gave a significant effect on the number of leaf yield and shoot height. The provision of BAP on basic MS medium with IAA of 1 ppm gave a significant effect on the number of shoots produced, the number of leaves produced, the length of the leaves, the width ofleaves and the length of shoots. The interaction of coconut water and BAP addition on MS base medium with IAA of 1 ppm gave significant effect on leaf length, leaf width and shoot length as well.Conclusions: MS + IAA basic media combined with coconut water + BAP could stimulate the growth of Sipahutar pineapple in vitro.Â Â